If the derivative of G ( x ) is ( x ln x ) 2 , and G ( e ) = 2 7 5 e 3 − 1 , find the value of G ( 1 3 ) .
Give your answer to 2 decimal places.
Clarification : e denotes Euler's number , e ≈ 2 . 7 1 8 2 8 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You can solve by using integration by parts twice
∫ u d w = u w − ∫ w d u
.
G ( x ) = ∫ x 2 ⋅ l n ( x ) 2 d x make the substitutions
.
u = l n ( x ) 2 , d u = 2 x − 1 ⋅ l n ( x ) d x
d w = x 2 d x , w = x 3 / 3
.
G ( x ) = ∫ x 2 ⋅ l n ( x ) 2 d x = 3 x 3 l n ( x ) 2 − 3 2 ∫ x 2 ⋅ l n ( x ) d x
Now to use integration by parts the second time. u(x) will be redefined
.
u = l n ( x ) , d u = x − 1 d x
d w = x 2 d x , w = x 3 / 3
.
∫ x 2 ⋅ l n ( x ) d x = 3 x 3 l n ( x ) − 3 1 ∫ x 2 d x = 3 x 3 l n ( x ) − x 3 / 9 + C
Substituting this into the first integral gets
.
G ( x ) = 3 x 3 [ l n ( x ) 2 − 3 2 l n ( x ) + 9 2 ] + C
G ( e ) = 2 7 5 e 3 + C = 2 7 5 e 3 − 1 , C = − 1
G ( x ) = 3 x 3 [ l n ( x ) 2 − 3 2 l n ( x ) + 9 2 ] − 1
Problem Loading...
Note Loading...
Set Loading...
G ( x ) ⟹ G ( e ) 2 7 5 e 3 − 1 ⟹ c ⟹ G ( x ) G ( 1 3 ) = ∫ ( x ln x ) 2 d x By integration by parts: u = ln 2 x , d v = x 2 d x = 3 x 3 ln 2 x − ∫ 3 x x 3 ⋅ 2 ln x d x By integration by parts again: u = ln x , d v = x 2 d x = 3 x 3 ln 2 x − 9 2 x 3 ln x + 9 2 ∫ x x 3 d x = 3 x 3 ln 2 x − 9 2 x 3 ln x + 2 7 2 x 3 + c c = constant = 2 7 x 3 ( 9 ln 2 x − 6 ln x + 2 ) + c = 2 7 e 3 ( 9 − 6 + 2 ) + c = 2 7 5 e 3 + c = − 1 = 2 7 x 3 ( 9 ln 2 x − 6 ln x + 2 ) − 1 ≈ 3 7 2 7 . 4 7